2012
DOI: 10.1103/physrevb.86.205102
|View full text |Cite
|
Sign up to set email alerts
|

Heterostructuring and strain effects on the infrared optical properties of nickelates

Abstract: An optical study of the effects of strain and heterostructuring on nickelates is presented. The optical conductivity data obtained for a series of ultrathin films of NdNiO 3 with varying amounts of strain reveal that two mechanisms, each associated with a different energy scale, are responsible for the tuning of the Drude-like spectral weight as a function of strain. Additionally, the optical properties of the LaNiO 3 layers in a LaNiO 3 /LaAlO 3 superlattice are investigated, showing that the coherent Drude t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Earlier angle-integrated photoemission studies of Nd 1−x Sm x NiO 3 show similar behavior of the spectral weight transfer from near E F region to higher binding energy region [36]. Our observation is also consistent with an optical study, where the MIT is argued to be linked to a spectral weight transfer from the Drude region (coherent state) to the deeper energy [11,31].…”
Section: )] the Loss Of Spectral Weight Near The Fermi Level Occurs supporting
confidence: 91%
See 1 more Smart Citation
“…Earlier angle-integrated photoemission studies of Nd 1−x Sm x NiO 3 show similar behavior of the spectral weight transfer from near E F region to higher binding energy region [36]. Our observation is also consistent with an optical study, where the MIT is argued to be linked to a spectral weight transfer from the Drude region (coherent state) to the deeper energy [11,31].…”
Section: )] the Loss Of Spectral Weight Near The Fermi Level Occurs supporting
confidence: 91%
“…The result is suggestive of the presence of a 'hidden' quantum critical point as a function of strain [6]. Interestingly, optical spectroscopies have identified that the MIT is associated with a spectral weight transfer from the mid-infrared region to a higher energy scale [11,31].…”
Section: Introductionmentioning
confidence: 95%
“…However, as some chemical nonstochiometry may be introduced during the growth, actual should be calculated using the experimentally measured lattice constant of an unstrained film (instead of a bulk ). The effect of strain on electronic and magnetic transitions of RENiO 3 series has been thoroughly explored by diverse experimental probes including thermal measurements and Hall effect measurement [58,64,65], synchrotron X-ray diffraction [66,67], X-ray absorption spectroscopy [67][68][69][70][71], resonant soft X-ray scattering [69,72,73], ARPES [74,75], optical spectroscopy [72,[76][77][78].…”
Section: A Epitaxial Strain In Ultra Thin Filmsmentioning
confidence: 99%
“…9(b)]. Considering a gap E g of 30-100 meV in the insulating phase of the NNO films [28,29], the Fermi level may reach the conduction band at the temperatures when the macroscopic metal-range conduction becomes observable on heating (Fig. 3).…”
Section: Localized Statesmentioning
confidence: 99%